2010
DOI: 10.1088/1758-5082/2/4/041001
|View full text |Cite
|
Sign up to set email alerts
|

Functional stability of endothelial cells on a novel hybrid scaffold for vascular tissue engineering

Abstract: Porous and pliable conduits made of biodegradable polymeric scaffolds offer great potential for the development of blood vessel substitutes but they generally lack signals for cell proliferation, survival and maintenance of a normal phenotype. In this study we have prepared and evaluated porous poly(ε-caprolactone) (PCL) integrated with fibrin composite (FC) to get a biomimetic hybrid scaffold (FC PCL) with the biological properties of fibrin, fibronectin (FN), gelatin, growth factors and glycosaminoglycans. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…The data indicate that PCL has the least tendency to turn thrombogenic, while the blend nanofibres have a high potential to become thrombogenic. One of the shortcomings in polymeric nanoconstructs used in cardiovascular tissue engineering is their propensity to activate blood coagulation, leading to thrombosis (Pankajakshan et al ., ). Our results have demonstrated that the aligned PCL nanofibrous scaffold has good non‐thrombogenic properties that are vital for the development of successful cardiovascular grafts.…”
Section: Resultsmentioning
confidence: 97%
“…The data indicate that PCL has the least tendency to turn thrombogenic, while the blend nanofibres have a high potential to become thrombogenic. One of the shortcomings in polymeric nanoconstructs used in cardiovascular tissue engineering is their propensity to activate blood coagulation, leading to thrombosis (Pankajakshan et al ., ). Our results have demonstrated that the aligned PCL nanofibrous scaffold has good non‐thrombogenic properties that are vital for the development of successful cardiovascular grafts.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the adherent platelets are round shape, which means they were nonactivated. As a widely used blood‐contacting biomaterial, the platelet adhesion of PET has also been tested. The adherent platelets on PET surface were 297 ± 41 cells per 10 4 μm 2 (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of adherent platelet on PNaAMPS/PAAm and PNaAMPS/PDMAAm hydrogels were 16 ± 7 and 9 ± 8 cells per 10 4 μm 2 , respectively. They were far less than the number of adherent platelet on polyethylene terephthalate (PET) (297 ± 41 cells per 10 4 μm 2 ), which is a widely used blood‐contacting biomaterial . Through the further investigations of the platelet adhesion mechanism, we found that the chemical components, zeta potential, and protein adsorption were the main influence factors on hydrogels platelet adhesion behavior.…”
Section: Introductionmentioning
confidence: 97%
“…Хорошая проникающая способность фибринового геля, крепкое сцепление с рельефной или пористой поверхностью после полимеризации позволяют использовать фибрин в качестве покрытия или пропитки каркасов из различных полимерных материалов или ксеногенной ткани [23,71,73]. В качестве полимерной основы биомиметического гибридного каркаса с биологическими свойствами фибрина используют пористый PCL [74], полилактид [71], PET [23], PTFE/дакрон [75]. Для сохранения механических свойств и улучшения биосовместимости разрабатывают биологические композитные каркасы на основе децеллюляризованных артерий, покрытых фибриновым гелем [73].…”
Section: низкая механическая прочность фибрина варианты решения пробunclassified